Angiotensin‐converting enzyme as a new immunologic target for the new SARS‐CoV‐2. Issue 2 (7th October 2020) - Hallaj, Shahin; Ghorbani, Anahita; Mousavi‐Aghdas, Seyed Ali; Mirza‐Aghazadeh‐Attari, Mohammad; Sevbitov, Andrey; Hashemi, Vida; Hallaj, Tooba; Jadidi‐Niaragh, Farhad
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has affected the daily lives of millions of people worldwide and had caused significant mortality; hence, the assessment of therapeutic options is of great interest. The leading cause of death among COVID‐19 patients is acute respiratory distress syndrome caused by hyperinflammation secondary to cytokine release syndrome (CRS). Cytokines, such as tumor necrosis factor‐α, interleukin‐6, interferon‐γ and interleukin‐10, are the main mediators of CRS. Based on recent evidence, the angiotensin‐converting enzyme (ACE) II is known to be the target of the COVID‐19 spike protein, which enables the virus to penetrate human cells. ACE II also possesses an anti‐inflammatory role in many pathologies such as cardiovascular disease, hypertension, diabetes mellitus and other conditions, which are the main risk factors of poor prognosis in COVID‐19 infection. Changes in tissue ACE II levels are associated with many diseases and hyperinflammatory states, and it is assumed that elevated levels of ACE II could aggravate the course of COVID‐19 infection. Therefore, the use of renin–angiotensin–aldosterone system inhibitors (RASis) in COVID‐19 patients could be hypothetically considered, though sufficient evidence is not presented by the scientific community. In this work, based on the most recent pieces of evidence, the roles of RAS and RASi in immunologic interactions are addressed. Furthermore, the molecular and immunologic aspects of RASi and their potential significance in COVID‐19 are discussed. Abstract : Here, we address the immunologic role of renin–angiotensin–aldosterone system and renin–angiotensin–aldosterone system inhibitor based on current and previous evidence aiming to improve the current knowledge regarding this system and its inhibition from molecular and immunologic perspectives.